Fixed Assets Management Supported by an ERP class IT System in Production Company - Karolina RYBICKA (Communications of International Proceedings, 2024)
In today's world, the business environment is extremely dynamic. Effective management of information and resources is crucial for a company to achieve success. One of the important elements in running a business are fixed assets, which constitute a significant part of the company's assets. Their proper management, recording and depreciation are crucial for the competitiveness and financial stability of the organization. The purpose of the paper is to highlight the gap, both in the literature and in the practical solutions available to the average user, in the field of recognition of fixed assets throughout their whole life cycle. The limitations of the IT system used, and the solution aimed at improving the management of fixed assets in the enterprise are presented in the paper. The paper is based on the literature study (both Polish and foreign authors) and analysis of case study in production company. For purpose of analysis the author considers detailed case study connected with fixed assets under construction, recognition and allocation of cost of construction and in next stage reliable assignment to proper objects. This process could be recognized as a challenge in this company, both among accounting staff and a construction department. In general, a management of fixed assets in an enterprise using ERP systems could be not very easy in special (not typical) cases and the author presents the challenges that may arise in an enterprise during the implementation of IT systems and the solutions that can be used.
Keywords: ERP; ICT technology; IT systems; Fixed Assets